Rational therapy for vaginal infections is a gynecologist's choice - М.S. Selikhova; T.I. Kostenko; A.A. Smol'yaninov (LCC «Medicine-Inform», 2022)
M.S. Selikhova, T.I. Kostenko, A.A. Smol'yaninov Volgograd State Medical University, Volgograd, Russian Federation Vaginal discharge is the most common reason for referral to a gynecologist. Given the polyetiological nature of vaginal infections, broad-spectrum medications are selected for treatment. Antiseptic solutions (whose efficacy is similar to antibiotics) included in Russian clinical guidelines for obstetrics and gynecology are now more favored. Chlorohexidine is the most studied antiseptic solution with established efficacy in obstetrics and gynecology, whose hallmark is the lack of inhibiting effects on Lactobacilli and local immunity. Combining chlorohexidine and dexpanthenol is one of the most promising therapeutic tools for bacterial vaginosis and vaginal infections. Dexpanthenol stimulates reparation and recovering vaginal and cervical mucosal integrity. This property is crucial for reducing inflammation and preventing recurrences. Recent multicenter randomized and observational study results have demonstrated high efficacy, safety, and good tolerability of combined preparation for vulvovaginitis of different etiologies and vaginal dysbiosis in women of reproductive age, postmenopausal and pregnant women, and while breastfeeding. Keywords: vaginal dysbiosis, vulvovaginitis, antiseptic, broad-spectrum, Lactobacilli, reparative. For citation: Selikhova M.S., Kostenko T.I., Smol'yaninov A.A. Rational therapy for vaginal infections is a gynecologist's choice. Russian Journal of Woman and Child Health. 2022;5(1):41-45 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-41-45.